Exposure to predator odor and resulting anxiety enhances the expression of the α2δ subunit of voltage‐sensitive calcium channels in the amygdala. (8th January 2013) - Nasca, Carla; Orlando, Rosamaria; Marchiafava, Moreno; Boldrini, Paolo; Battaglia, Giuseppe; Scaccianoce, Sergio; Matrisciano, Francesco; Pittaluga, Anna; Nicoletti, Ferdinando
Abstract The α2δ subunit of voltage‐sensitive calcium channels (VSCCs) is the molecular target of pregabalin and gabapentin, two drugs marked for the treatment of focal epilepsy, neuropathic pain, and anxiety disorders. Expression of the α2δ subunit is up‐regulated in the dorsal horns of the spinal cord in models of neuropathic pain, suggesting that plastic changes in the α2δ subunit are associated with pathological states. Here, we examined the expression of the α2δ‐1 subunit in the amygdala, hippocampus, and frontal cortex in the trimethyltiazoline (TMT) mouse model of innate anxiety. TMT is a volatile molecule present in the feces of the rodent predator, red fox. Mice that show a high defensive behavior during TMT exposure developed anxiety‐like behavior in the following 72 h, as shown by the light–dark test. Anxiety was associated with an increased expression of the α2δ‐1 subunit of VSCCs in the amygdaloid complex at all times following TMT exposure (4, 24, and 72 h). No changes in the α2δ‐1 protein levels were seen in the hippocampus and frontal cortex of mice exposed to TMT. Pregabalin (30 mg/kg, i.p.) reduced anxiety‐like behavior in TMT‐exposed mice, but not in control mice. These data offer the first demonstration that the α2δ‐1 subunit of VSCCs undergoes plastic changes in a model of innate anxiety, and supports the use of pregabalin as a disease‐dependent drug in the treatment of anxiety disorders.